(untitled) (Annals of Medical Research, 2022)
Aim: The main objective of our study was to examine the protection of misoprostol (MP) on paclitaxel (PTX) side effects in rat ovaries. Materials and Methods: Twenty-one female Sprague-Dawley rats were provided to form 3 groups, each containing seven rats: In group 1 (control group), was given 1 mL of 0.9% NaCl intraperitoneally (i.p.) and 1 mL of 0.9% NaCl orally for 6 days. In treatment groups, each rat was injected 2 mg/kg PTX i.p. on days 0, 2, 4, and 6 of the study and 0.2 mg/kg/day MP was given by oral gavage for 6 days. Results: Levels of malondialdehyde (MDA), and glutathione (GSH), activities of superoxide dismutase (SOD), and catalase (CAT) of tissue samples were measured. Histopathological alterations in PTX administrated rats were seen such as, degenerative changes in granulosa cells, decrease in number of growing and tertiary follicles and increasing active caspase 3 (Casp-3) positive immunoreaction in theca, granulosa and stromal cells. Conclusion: As a result, it shows that the use of MP can improve PTX-induced ovarian damage by preventing oxidative damage.